PELATIHAN DESAIN PACKAGING DENGAN CANVA DAN WEPIK - Misnan, Misnan; Sukma, Agus Hitopa; Riyantie, Mayang; Hamboer, Maria Jashinta Elisabet; Barizki, Rezzi Nanda (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service has the aim of practical and interactive design training regarding packaging design using Canva and Wepik and a form of providing counseling to help the MSME group of the Indonesian Congregational Success Community (KSBI) in South Jakarta in developing packaging design skills and improving the quality and visual appeal of products resulting from. In this activity there are 5 (five) stages, namely training and counseling through: 1) Introduction to packaging design, 2) Introduction to Canva and Wepik, 3) Practice packaging design with Canva and Wepik. The implementation methods: 1) counseling and presentation regarding the importance of attractive and effective packaging design, 2) practical demonstration using the Canva and Wepik platforms to design packaging, 3) interactive training session, where participants can try directly to create their own packaging design, 4) discussion and questions and answers to clarify packaging design concepts and techniques. The results obtained through this community service consist of: a) training participants have a good understanding of the importance of attractive and effective packaging design, b) participants are able to use Canva and Wepik to create professional packaging designs, c) MSMEs are members of KSBI Jakarta The South can implement packaging designs that are tailored to their products, d) increase the competitiveness and marketing of KSBI member MSME products through attractive packaging designs.